Miniatur Toleransi Kerjasama Muslim-Kristen di Klinik Sang Timur Pabian Sumenep - Achmad Bahrur Rozi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
Known as devout muslims have not made Maduras people intolerant to other religious people. The tolerance of Madura people toward members of other faiths is evidenced by the fact that all religions in Madura, such as Christianity, Hinduism, Buddhism, Confucius and Catholicism are safe and thriving in Madura. A manifestation of tolerance in Madura is evidenced in the harmonizing of three different religious communities in the village of Pabian Sumenep. The study will explain a model of Muslim tolerance at the Klinik Sang Timur Pabian Sumenep. What are the factors that underlie the establishment of cooperation tolerance of Muslim-Christian at the Klinik Sang Timur Pabian Sumenep. The study uses a qualitative approach with data collection techniques of library research, observation, interviews, and documentation. Theory relevant to researchers is the study of the meaning of action. The conclusion of the study is this: Tolerance that takes place in the Klinik Sang Timur is not a indifferent, compassion and pity. Tolerance in the practice of Klinik Sang Timur is the majority tolerance for a minority belonging to be part of community together. Tolerance in the Klinik Sang Timur is categorized in the post level of tolerance that not only forms mutual respect but savoring other ethical principles as a valuable choice. Tolerance at the Klinik Sang Timur stems from the tradtion and local wisdom which are firmly rooted.